Random House Webster's computer & internet dictionary - Margolis, Philip E. (New York : Random House, 1999)
Rev. ed. of: Random House personal computer dictionary. 2nd ed. c1996.
Keywords: Microcomputers -- Dictionaries; Computers -- Dictionaries